LAND OWNERSHIP STRUCTURE OF THE SOUTHWESTERN PART OF SERBIA - Jandrić, Mersida; Hadrović, Sabahudin; Rakonjac, Ljubinko; Ćosić, Milivoje (ACADEMIC REVIEW, 2021)
The average property in the Republic of Serbia is 5.44 ha, which is far below the average at the EU level, which is 17.7 ha. This fragmentation of holdings prevents technological progress, which automatically leads to unprofitability, low income and uncompetitiveness of agricultural production compared to developed countries. All this accelerates the demographic emptying of villages and the overpopulation of cities, with which some major problems arise. The fact that agricultural land is the most important factor in agricultural production led the authors to conduct research in the territories of Sjenica, Tutin and Novi Pazar and analyze the ownership structure of land. Almost the entire territory of Sjenica is located on the Pešter plateau, Tutina for the most part, while Novi Pazar only rests on the aforementioned plateau. The authors considered that it is illogical to conduct research in Tutin and Sjenica, and exclude the city of Novi Pazar for the reason that almost all distribution and marketing of agricultural production is done from Novi Pazar. In fact, it is also about farms, entrepreneurs and other business entities that perform a part of production-related activities on the Pešter Plateau - where a lot of the workforce is engaged from Novi Pazar, and all the rest are performed from Novi Pazar.